2018
DOI: 10.2298/vsp161010012i
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities of retrograde intrarenal surgery in the treatment of renal lower pole stones in children

Abstract: Background/Aim. Renal stones located in the lower pole of kidney represent a serious challenge for surgical treatment in children. The options are: open surgery, extracorporeal shock-wave lithotripsy, percutaneous nephrolithotomy and retrograde intrarenal surgery. Reports about the endoscopic treatment in children are limited. The aim of the study was to evaluate the effectiveness of retrograde intrarenal surgery in pediatric patients with renal stones in lower pole of the kidney. Methods. We retrospectively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Study by Ilic, et al (2016) showed the length of time spent under anesthesia, the requirement for additional treatment, the average length of stay in the hospital, and the incidence of mild complications such as perirenal haematoma, urinoma, and limited ureteral perforation were all considerably reduced in the LL group (p <0.05). We discovered that there was a statistically significant difference between the stone-free rates of the two groups; the LL group had a considerably higher stone-free rate than the PL group (LL: 94.4% vs. PL: 62.5%) (p <0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study by Ilic, et al (2016) showed the length of time spent under anesthesia, the requirement for additional treatment, the average length of stay in the hospital, and the incidence of mild complications such as perirenal haematoma, urinoma, and limited ureteral perforation were all considerably reduced in the LL group (p <0.05). We discovered that there was a statistically significant difference between the stone-free rates of the two groups; the LL group had a considerably higher stone-free rate than the PL group (LL: 94.4% vs. PL: 62.5%) (p <0.05).…”
Section: Resultsmentioning
confidence: 99%
“…We discovered that there was a statistically significant difference between the stone-free rates of the two groups; the LL group had a considerably higher stone-free rate than the PL group (LL: 94.4% vs. PL: 62.5%) (p <0.05). 11 Other study cnducted with 45 consecutive patients treated with FURSL developed PRH. Patients with PRH had a lower body mass index (20.2 ± 3.2 kg/m2 vs 26.9 ± 5.5 kg/m2, p = 0.015), a thinner kidney cortex thickness (0.88 ± 0.41 cm vs 1.39 ± 0.41 cm, p = 0.024), and a history of chronic kidney disease (75% vs 14.6%, odds ratio [OR] = 17.5, 95% confidence interval [CI] = 1.55-197.46, p = 0.021).…”
Section: Resultsmentioning
confidence: 99%